Biochemical and radical-scavenging properties of sea cucumber (Stichopus vastus) collagen hydrolysates - Abedin, Md. Zainul; Sarker, Md. Zaidul Islam (Taylor & Francis Ltd, 2014)
The molecular mass distribution, amino acid composition and radical-scavenging activity of collagen hydrolysates prepared from collagen isolated from the sea cucumber Stichopus vastus were investigated. b and a1 chains of the collagen were successfully hydrolysed by trypsin. The molecular mass distribution of the hydrolysates ranged from 5 to 25 kDa, and they were rich in glycine, alanine, glutamate, proline and hydroxyproline residues. The hydrolysates exhibited excellent radical-scavenging activity. These results indicate that collagen hydrolysates from S. vastus can be used as a functional ingredient in food and nutraceutical products.